Diagenetic Screening in Porites Fossil Corals from South Pagai, Kendari, and Banten Bay, Indonesia - Dwi Amanda Utami; Sri Yudawati Cahyarini (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Fossil corals are commonly used in paleoclimate studies to get records of climate parameters throughout the Holocene and beyond. Diagenesis is known as an important error source in paleoclimate reconstruction. The aim of this research was to provide a comprehensive diagenetic investigation involving 2D-XRD, petrographic analysis, and scanning electron microscopy (SEM) of Porites spp fossil samples from South Pagai, Kendari and Banten Bay, Indonesia as a starting point for further climate studies using coral proxies. This research focused on samples with around 1% calcite content, a level that can create misinterpretation of geochemical proxies. The results indicate that the samples from Banten Bay and South Pagai are well preserved and reliable for paleoclimate study. Only Sample BG1 is not recommended for further use in geochemical proxy analysis due to intensive diagenesis. 2D-XRD allows calcite screening without destroying the coral sample and assists in defining alternative sampling transects. Secondary aragonite and dissolution cannot be identified with 2D-XRD, therefore diagenetic screening should be combined with petrographic and SEM analysis in any areas presumed to have diagenetic textures.